A comparative performance analyze model and supplier positioning in performance maps for supplier selection and evaluation - Bilişik, Mutlu Emir; Çağlar, Hatice Nazan; Alp Bilişik, Özge Nalan (Elsevier Science Bv, Sara Burgerhartstraat 25, Po Box 211, 1000 AE Amsterdam, Netherlands, 2012)
In supply chain, supplier has an important role and in this situation supplier evaluation and selection is gained more significance for companies. So that, it is purposed to improve an evaluation model to evaluate and select suppliers more effectively by correlate with company's supply chain. For that reason, a form is designing to collect data from concerned company's personnel and performance measuring model which includes scoring methodology and correlation analysis that is called as "Performance-Effect" analysis in this study. With this model, it is proposed to divest supplier evaluation from its general evaluation concept by presenting alternative selection criteria, suppliers and methods for working with positioning of these in performance maps.
Keywords: Supplier evaluation; Supplier selection; supplier performance; performance-effect analysis; supplier positioning